Whole-Genome Analysis of Individual Meiotic Events in Drosophila melanogaster Reveals That Noncrossover Gene Conversions Are Insensitive to Interference and the Centromere Effect. Issue 1 (1st May 2016) - Miller, Danny E; Smith, Clarissa B; Kazemi, Nazanin Yeganeh; Cockrell, Alexandria J; Arvanitakis, Alexandra V; Blumenstiel, Justin P; Jaspersen, Sue L; Hawley, R Scott
Abstract: A century of genetic analysis has revealed that multiple mechanisms control the distribution of meiotic crossover events. In Drosophila melanogaster, two significant positional controls are interference and the strongly polar centromere effect. Here, we assess the factors controlling the distribution of crossovers (COs) and noncrossover gene conversions (NCOs) along all five major chromosome arms in 196 single meiotic divisions to generate a more detailed understanding of these controls on a genome-wide scale. Analyzing the outcomes of single meiotic events allows us to distinguish among different classes of meiotic recombination. In so doing, we identified 291 NCOs spread uniformly among the five major chromosome arms and 541 COs (including 52 double crossovers and one triple crossover). We find that unlike COs, NCOs are insensitive to the centromere effect and do not demonstrate interference. Although the positions of COs appear to be determined predominately by the long-range influences of interference and the centromere effect, each chromosome may display a different pattern of sensitivity to interference, suggesting that interference may not be a uniform global property. In addition, unbiased sequencing of a large number of individuals allows us to describe the formation of de novo copy number variants, the majority of which appear to be mediated by unequal crossing over between transposable elements. This work has multiple implications for our understanding of how meiotic recombination is regulated to ensure proper chromosome segregation and maintain genome stability.